Development Of Fluorescing Methicillin Resistant Staphylococcus Aureus (Mrsa) As A Tool For The Screening Of Antibacterial Properties Of Mimusops Elengi Linn - Zaabar, Wan Razlin Wan (2011)
Staphylococcus aureus is a Gram positive bacterium that can cause abscesses, various pyogenic infections (e.g. endocarditis and osteomyelitis), food poisoning and toxic-shock syndrome. It is also one of the most common causes of nosocomial infection (pneumoniae, septicaemia and surgical-wound infections). The Methicillin Resistant Staphylococcus aureus (MRSA) is a strain that is resistant to β-lactam antibiotic by virtue of changes in the penicillin-binding protein within their cell membrane. Consequently, all antibiotics that has β-lactam ring like penicillin group and cephalosporin group are unable to inhibit the growth of this organism. Green fluorescent protein (GFP) is a protein of unknown function found in the jellyfish, Aequorea victoria. This GFP-fusion protein shows a punctuate pattern when localizes in the cytoplasm. The present study focused on the development of a fluorescing MRSA by the construction of MRSA vector carrying GFP gene with the intention of determining whether the fluorescing MRSA strain can be used as a tool for the rapid screening of antibacterial properties of natural product. The natural products that had been used were aqueous and several organic solvents extracts from the bark of plant Mimusops elengi Linn. known locally as ‘Bunga Tanjung’ plant. This plant has been reported to contain a potent antibacterial component. In this study, phytochemical investigation of aqueous, ethanolic and ethyl acetate extracts of M. elengi Linn. revealed the presence of alkaloids, flavonoids and tannin compounds. Whereas, the diethyl ether and petroleum ether extracts revealed the presence of alkaloids only but absence of flavonoids and tannin compounds. These secondary metabolites are known to be synthesized in response to microbial infection.